An Ultra-Low Power, Adaptive All-Digital Frequency-Locked Loop With Gain Estimation and Constant Current DCO - Imran Ali; Hamed Abbasizadeh; Muhammad Riaz Ur Rehman; Muhammad Asif; Seong Jin Oh; Young Gun Pu; Minjae Lee; Keum Cheol Hwang; Youngoo Yang; Kang-Yoon Lee (IEEE Access)
In this paper, an ultra-low power, adaptive all-digital integer frequency-locked loop (FLL) with gain estimation and constant current digitally controlled oscillator (DCO) for Bluetooth low energy (BLE) transceiver in Internet-of-Things (IoT) is presented. For locking DCO frequency closest to the target channel, it adaptively controls capacitor banks with binary algorithm. With decrease in frequency resolution, DCO clock counts for each capacitor bank bit evaluation dynamically increases with the proposed technique for accurate frequency tracking. For compensating PVT variations and finding the BLE frequency deviation, the configurable digital DCO gain estimation is incorporated. The low power and constant current DCO operates in sub-threshold region and its power consumption is minimized by $g_{m}/I_{D}$ methodology optimization, constant current source for limiting current in DCO core through adaptive low-dropout regulator (LDO) and lowering the supply voltage. The proposed design is integrated in an ADPLL for BLE transceiver and it is fabricated with 1P6M TSMC 55 nm CMOS technology. The all-digital adaptive FLL is fully synthesizable and its area is $1800~μ \text{m}^{2}$ with 1.233 K gate count. The RMS current consumption is $103.32~μ \text{A}$ from 1 V voltage supply with $103.32~μ \text{W}$ power requirement. The experimental results reveal, DCO draws $480~μ \text{A}$ current from 0.55 V supply voltage at center frequency. It has frequency resolution of 4.8 kHz. The oscillator PN, FOM and FOMT at 1-MHz offset frequency from 2.44 GHz carrier frequency are −122.85 dBc/Hz, 196.38 dBc/Hz and 208.19 dBc/Hz, respectively.